AN EXAMINATION OF INTEGRATIVE ISLAMIC EDUCATION AT SMP INTEGRAL HIDAYATULLAH KENDARI - Basri, Hasan; DM, Herman; Ilham, Ilham; Saleh, Muhammad (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
The integrative curriculum plays a crucial role in fostering a holistic learning experience by amalgamating general knowledge with religious values. This research constitutes a case study of the integrative curriculum framework at Hidayatullah Kendari Integral Junior High School, aiming to elucidate the curriculum content, presentation methodologies, and pedagogical strategies employed by teachers to incorporate religious elements into educational materials and activities. Data were collected through document analysis, observations, and interviews with school administrators and teachers. The data analysis procedure involved verifying and categorizing the data, presenting it in accordance with the research questions, conducting a comprehensive analysis using curriculum integration theory and prior research findings, and drawing conclusions. The findings reveal that the school's curriculum, grounded in Qur'anic principles, continues to incorporate the government curriculum as its core, augmented by local content and religious development. The integration of religion into the educational process employs a connected model, utilizing pedagogical methods that align with Islamic educational principles, thereby enabling students to contextualize the acquired knowledge within a religious framework. The implications of this study suggest that teachers must enhance their religious knowledge in tandem with their subject matter expertise. Furthermore, religious educators provide additional religious instruction beyond regular school hours, necessitating students' residency in the school dormitory. Abstrak: Kurikulum integratif memainkan peran penting dalam menciptakan pengalaman belajar yang holistik dengan menggabungkan ilmu pengetahuan umum dan nilai-nilai keagamaan. Penelitian ini merupakan studi kasus terhadap format kurikulum integratif di SMP Integral Hidayatullah Kendari, dengan tujuan mendeskripsikan format muatan kurikulum, metode penyajian, dan teknik yang digunakan oleh guru dalam mengintegrasikan agama ke dalam materi dan kegiatan pembelajaran. Data dikumpulkan melalui analisis dokumen, observasi, dan wawancara dengan kepala sekolah dan guru. Proses analisis data melibatkan verifikasi dan sortir data, penyajian data sesuai dengan pertanyaan penelitian, pendalaman menggunakan teori integrasi kurikulum serta temuan penelitian sebelumnya, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa format kurikulum di sekolah ini berbasis pada al-Qur’an dengan tetap mengadopsi kurikulum pemerintah sebagai kurikulum inti, yang dilengkapi dengan muatan lokal dan pengembangan keagamaan. Integrasi agama dalam pembelajaran menggunakan model connected, di mana metode-metode pengajaran diintegrasikan dengan metode-metode pendidikan dalam Islam. Dengan demikian, kegiatan pembelajaran membantu siswa memahami pengetahuan yang diajarkan secara kontekstual berdasarkan ajaran agama. Implikasinya, guru harus meningkatkan pengetahuan keagamaan mereka seiring dengan peningkatan pengetahuan terhadap mata pelajaran. Guru agama juga memberikan pelajaran tambahan di luar jam sekolah, yang mengharuskan siswa untuk tinggal di asrama sekolah.